2017
DOI: 10.1007/s00105-017-3950-3
|View full text |Cite
|
Sign up to set email alerts
|

Erstmanifestation eines Ulcus cruris

Abstract: Based on the findings of our study, it is possible to limit the underlying etiology on the basis of the age of first manifestation of the leg ulcer in order to make targeted diagnostics more effective. Thus, this information can help to optimize scarce time resources in daily practice and improve the prediction probability of leg ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the majority of previous studies, BCC was the most common type of malignancy found in chronic leg ulcers, followed by SCC [ 4 , 5 , 6 , 7 , 8 ]. This is in accordance with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of previous studies, BCC was the most common type of malignancy found in chronic leg ulcers, followed by SCC [ 4 , 5 , 6 , 7 , 8 ]. This is in accordance with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation of chronic leg ulcers is a rare but possible condition, with squamous cell carcinomas (SCC) being the most common tumour type developing in chronic leg ulcers [ 3 ]. The prevalence of malignancy in chronic leg ulcers in the literature ranges from 2.0% to 2.8% in retrospective analyses [ 4 , 5 , 6 ] and 4% to 10.4% in prospective studies [ 7 , 8 ]. The two most common types of ulcerating skin tumours are basal cell carcinoma (BCC) and SCC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 They manifest on the lower limb and represent between 60% and 80% of all leg ulcerations. 2,3 Their three-months healing rate is estimated at 40% 4 and once healed up to 80% of patients develop a recurrence within 3 months. 5 The prevalence of VLUs is are reported around 1.08% 6 and the incidence being up to 1.33%.…”
Section: Introductionmentioning
confidence: 99%
“…Venous leg ulcers (VLU) are a major clinical challenge and the result of chronic venous insufficiency (CVI) and venous hypertension 1 . They manifest on the lower limb and represent between 60% and 80% of all leg ulcerations 2,3 . Their three‐months healing rate is estimated at 40% 4 and once healed up to 80% of patients develop a recurrence within 3 months 5 .…”
Section: Introductionmentioning
confidence: 99%